2010
DOI: 10.1182/blood-2010-06-288589
|View full text |Cite
|
Sign up to set email alerts
|

FIP200 is required for the cell-autonomous maintenance of fetal hematopoietic stem cells

Abstract: Little is known about whether autophagic mechanisms are active in hematopoietic stem cells (HSCs) or how they are regulated. FIP200 (200-kDa FAK-family interacting protein) plays important roles in mammalian autophagy and other cellular functions, but its role in hematopoietic cells has not been examined. Here we show that conditional deletion of FIP200 in hematopoietic cells leads to perinatal lethality and severe anemia. FIP200 was cell-autonomously required for the maintenance and function of fetal HSCs. FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
195
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 210 publications
(222 citation statements)
references
References 51 publications
16
195
0
3
Order By: Relevance
“…Moreover, as the results of this study suggest, adult stem cells appear to be not only able to tolerate a certain degree of stress but also to be ready to initiate regeneration and repair of tissues that were damaged as a consequence of cytotoxic treatment. Our observations are in agreement with recent reports demonstrating impaired production of lymphoid and myeloid progenitors in mice with autophagy-deficient HSC [1,2]. However, in these previous experimental mouse studies, the defect in differentiation might have been due to insufficient stem cell maintenance.…”
Section: Dear Editorsupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, as the results of this study suggest, adult stem cells appear to be not only able to tolerate a certain degree of stress but also to be ready to initiate regeneration and repair of tissues that were damaged as a consequence of cytotoxic treatment. Our observations are in agreement with recent reports demonstrating impaired production of lymphoid and myeloid progenitors in mice with autophagy-deficient HSC [1,2]. However, in these previous experimental mouse studies, the defect in differentiation might have been due to insufficient stem cell maintenance.…”
Section: Dear Editorsupporting
confidence: 94%
“…For instance, FIP200 (200 kDa focal adhesion kinase family interacting protein) was shown to be essential not only for the induction of autophagy, but also for the maintenance and function of HSC in vivo [1]. Moreover, HSC lacking autophagy-related gene (ATG) 7, another essential autophagy protein, were also unable to survive under in vivo conditions [2].…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Two hESC lines (CHA15-hESC [23], passages 55-85, and H9, passages 50-80) and a human induced pluripotent stem cell (iPSC) line [24] (passages [25][26][27][28][29][30][31][32][33][34][35] were used in this study. They were maintained on Mitomycin C (Sigma-Aldrich, St. Louis, MO, http://www.sigmaaldrich.com)-treated mouse embryonic fibroblasts (mct-MEFs) in the ESC medium at 37 C and 5% CO 2 in air.…”
Section: Chemical Treatments In Hescsmentioning
confidence: 99%
“…With the increased ROS, cancer cells induce antioxidant programs to set a new redox balance, resulting in cellular adaptation. Studies have shown that autophagic inhibitor (chloroquine) caused accumulated ROS in cells, and downstream of Atg1, FIP200-(Atg17 homologue) knockout livers, and Atg5-and Atg7-knockout cells both increase ROS production [25][26][27][28][29][30]. On the basis of these results, we hypothesized that there is a possibility that autophagy inhibition not only leads to accumulation of p62 to activate Nrf2 pathway by a noncanonical way but also increase ROS production to directly activate Nrf2 pathway.…”
Section: Introductionmentioning
confidence: 92%